PENGARUH KEMAMPUAN SISWA MENYELESAIKAN SOAL HOTS DAN LINGKUNGAN SOSIAL TERHADAP KREATIVITAS SISWA KELAS XI KOMPETENSI KEAHLIAN OTOMATISASI DAN TATA KELOLA PERKANTORAN SMK NEGERI 1 KUDUS - Lu'luil Maxnun; Hery Sawiji; Patni Ninghardjanti (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2021)
This study aims to determine whether: : (1) there is a positive and significant influence between students ability to complete HOTS on student’s creativity (t_hitung > t_tabel atau 3,754 > 1,995; (2) there is a positive and significant influence between social environment on student’s creativity (t_hitung> t_tabel atau 9,748 > 1,995); (3) there is a positive and significant influence between students ability to complete HOTS and social environment on student’s creativity (F_hitung> F_tabel atau 116.634 > 3,128). This research uses a quantitative approach with a survey method. Population 72 people. The sampling technique uses purposive saturated sample. The data is then processed using IBM SPSS 25. This analysis includes the validity test, reliability test, classical assumption test and hypothesis testing.The results of this study are, students ability to complete HOTS has a positive and significant effect on student’s creativity. Social environment has a positive and significant effect on student’s creativity. Students ability to complete HOTS and Social environment have a simultaneous influence on student’s creativity. Keywords: HOTS, social environment, and creativity